CHANGES IN A-AMYLASE ACTIVITY OF ORAL FLUID IN THE PROCESS OF COMPLEX TREATMENT OF PATIENTS WITH ISCHEMIC HEART DISEASE WITH DEFECTS OF DENTITION - N. Riabushko; V. Dvornik; A. Baranova; G. Balia (Український стоматологічний альманах)
There was indicated that disorders of regional circulation and microcirculation are significant in violation of oral homeostasis. The main indicators displaying the functioning of the mouth as biological system are enzymes and indexes of immune system.